The Pengaruh Perceived Organizational Support, Need for Achievement dan Transformational Leadership terhadap Employee Performance: Merit System sebagai Moderator - Izati, Nurul; Azhar; Prabujaya, Sena Putra (Jurnal Manajemen dan Organisasi, 2024)
Employee performance is multidimensional, comprising in-role performance and extra-role performance combined to measure it holistically. This study aims to examine the influence of Perceived Organizational Support (POS), Need for Achievement, and Transformational Leadership on Employee Performance with Merit System as a moderating variable in the North Musi Rawas District Government. Based on the Slovin formula (10 percent margin of error), the minimum sample size is 96 Civil Servants selected using non-probability sampling technique (convenience sampling). Data analysis is conducted using Structural Equation Modeling (SEM) Partial Least Square (PLS) with the assistance of SmartPLS version 4 for Windows software. The study findings indicate a positive and significant influence of Perceived Organizational Support (POS) and Need for Achievement on Employee Performance. However, the influence of Transformational Leadership on Employee Performance shows a negative albeit insignificant result. Additionally, no significant influence is found from the Merit System as a moderating variable on the relationship between POS, Need for Achievement, Transformational Leadership, and Employee Performance. These emphasize the importance of strengthening organizational support, developing appropriate training programs, implementing a better merit system, and aligning leadership styles with organizational conditions to enhance public sector employee performance.